Identification of CYP46A1 as a new regulator of lipid metabolism through CRISPR‐based whole‐genome screening. Issue 10 (20th August 2020) - Si, Zhongzhou; Guan, Xinjie; Teng, Xiangyun; Peng, Xiaoxia; Wan, Zhengqin; Li, Qiang; Chen, Guangshun; Tan, Jieqiong; Li, Jiequn
Abstract: Abnormal lipid droplet (LD) metabolism causes a variety of disorders, especially to nonalcoholic fatty liver disease (NAFLD). But the mechanism of abnormal aggregation of LD is still not fully elucidated. Here, Genome‐wide CRISPR‐Cas9 knockout (GeCKO) screening was employed to identify candidate genes regulating LD metabolism in L02 cell. We analyzed simultaneously the transcriptomics of liver tissues of NAFLD to find potential genes involved in pathogenesis of NAFLD. After integration these data, we found that the expression of 43 candidate genes from the GeCKO screening was also decreased in tissues of NAFLD patients. Many of these 43 overlapping genes have been reported to play an important role in the formation of LD. Subsequently, we focused on CYP46A1, one of 43 candidate genes and mitochondria‐related genes. We confirmed that the protein expression of CYP46A1 is deceased in tissues of NAFLD patients. Downregulation or overexpression of CYP46A1 affected LD accumulation in vitro. Deficiency of CYP46A1 impaired mitochondrial morphology and function, which may be responsible for the accumulation of LD. In summary, this study explored regulatory factors of LD accumulation at the whole‐genome level, and demonstrated that CYP46A1 regulated LD formation involving in NAFLD pathogenesis. It provides new clues for studying the molecular mechanisms of diseases related to abnormal lipid metabolism.